A Three-Phase Top- Query Based Distributed Data Collection Scheme in Wireless Sensor Networks - Guorui Li; Jingsha He; Cong Wang (International Journal of Distributed Sensor Networks)
We propose a three-phase top- k query based distributed data collection scheme which is designed for clustered or multisink wireless sensor networks. The proposed scheme consists of a distributed iterative hard thresholding algorithm and a three-phase top- k query algorithm. In the distributed iterative hard thresholding algorithm, the cluster heads or sink nodes reconstruct the compressed data in a distributed and cooperative manner. Meanwhile, the top- k query operation in the above algorithm is realized by pruning unnecessary elements among cluster heads or sink nodes in the three-phase top- k query algorithm. Simulation results show that there is no obvious difference in the performance of data reconstruction between our proposed scheme and existing compressive sensing theory based data collection schemes. However, both the number of interactions and the amount of transmitted data among cluster heads or sink nodes can be effectively reduced in the proposed scheme. The performance of the proposed scheme is analyzed in detail in this paper to support the claims.